Pendidikan Islam Menurut al-Nadwi: Satu Analisis - El-Muhammady, Muhammad ’Uthman (Jurnal Usuluddin, 2000)
The paper deals with al-Nadwi’s thought on the concept of the Islamic education. This includes the importance of education based on the Qur’an, the Sunnah and other Islamic basic foundations. It also discusses about the concept of Islamic university and his view on modern sciences.